Improved bioassays using a local effect, such as muscle paralysis, as an endpoint. (1st June 2015) - Cevc, Gregor
Abstract: Drug potency testing consumes many animals, botulinum neurotoxin (BoNT) testing being perhaps the most notorious example. To avoid 50% lethal dose determination, the so-called digital abduction score (DAS) and other BoNT induced local paralysis assays were developed. This paper reveals that a simple mathematical expression — the Bateman's equation used in many pharmacokinetic data analyses — can describe in full detail the time dependence of the BoNT induced local paralysis; the equation hence allows robust interpolation and extrapolation, as well as integral effect (AUC), and its dose dependence, evaluation. The equation is moreover a convenient tool for experimental planning and for extracting, from experimental data, the parameters that characterise BoNT potency. Most important, one can generally reduce the number of animals needed to gain reliable results at least 20–33% (and possibly 50% or even 75%) by analysing and modelling the time course of a local effect (such as muscle paralysis) with the equation, rather than just by averaging the maximum observed effect size at one point in time.